Distributed multimedia applications / Safawi Abdul Rahman - Abdul Rahman, Safawi (Faculty of Information Management, 2005)
This article is a compilation work and outlines the overview of distributed multimedia applications. The main goal of this work is to enlighten the dissimilarities between multimedia and distributed multimedia. It encompasses a brief overview of multimedia and in contrast, a somewhat extensive discussion on distributed multimedia. This work emphasizes the concept of distributed multimedia, its applications, benefits of using it, technologies to support it and the vulnerabilities of distributed multimedia. Even though researchers and other scholars have been advanced and explored a wide range of distributed multimedia applications and its scope, this work is considered useful to the beginners and to those who are new to this area.